Angiotensin-Converting Enzyme Gene Insertion/Deletion Polymorphism and Its Association with the Severity of Preeclampsia - Tulmaç, Özlem Banu; Uğurlu, Evin Nil; Zülfikaroğlu, Ebru (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: Pre-eclampsia is a multisystemic, idiopathic pregnancy-specific disorder. The role of inappropriate activation of renin-angiotensin system is well known. In this study it is aimed to elucidate the relationship between angiotensin converting enzyme (ACE) gene insertion/deletion polymorphism and severity of pre-eclampsia. STUDY DESIGN: Pre-eclamptic or eclamptic 43 women who were either nulliparous or had been preeclamptic in their first pregnancy have been included to the study. It was a cross sectional observation study. Thorough obstetric examination was done for each patient. Demographic properties, laboratory findings, gestational ages and obstetric histories were recorded. Obstetric ultrasonographies were performed. Of the 43 patients included, 24 (55.8%) were suffering from severe pre-eclampsia. Other 19 (44.2%) patients were not severely ill. A correlation between preeclampsia severity and ACE gene polymorphism was not found. DD genotype was associated with higher systolic blood pressures (p=0.04). CONCLUSION: In our study, in order to predict pre-eclampsia severity use of ACE gene polymorphism has noyt been established. DD genotype was found to be a risk factor for systolic blood pressure increment in pre-eclamptic pregnants. Randomized, prospective studies with large populations are needed on this subject.